Primary Cutaneous B-Cell Lymphomas: An Update - Vitiello, Paola; Sica, Antonello; Ronchi, Andrea; Caccavale, Stefano; Franco, Renato; Argenziano, Giuseppe (Frontiers in Oncology, 2020)
Primary Cutaneous B cell lymphomas (PCBCLs) comprise a group of extranodal B-cell non-Hodgkin lymphomas B cell derived which primarily involve the skin without evidence of extracutaneous disease at the time of diagnosis. They include approximately 25% of all cutaneous lymphomas and are classified in three major subgroups (World Health Organization (WHO) 2017): primary cutaneous marginal zone lymphoma (PCMZL), primary cutaneous follicle-center cell lymphoma (PCFCL) and diffuse large B cell lymphoma, leg type (PCDLBCL, LT). This classification also includes some less common entities such as intravascular large B cell lymphoma. Recently, WHO-EORTC added Epstein-Barr virus positive (EBV+) mucocutaneous ulcer, as new provisional distinct entity, to cutaneous B cell lymphomas. PCBCLs are classically characterized by patches, plaques or nodules showing great variability for color, shape and location. Diagnosis requires histological examination with immunohistochemical staining. In general, therapeutic options depend on the exact histological, immunohistochemical classification, on the disease presentation and on the risk assessment. PCMZL and PCFCL are considered indolent lymphomas with a good prognosis and are associated with 5-year disease-specific survival ≥ 95%. In contrast, PCDLBCL leg-type is considered an aggressive lymphoma with a survival rate in 5 years lower than 60%. Patients with a solitary lesion or limited lesions in a single anatomical site, require different treatments than patients with generalized lesions or refractory disease or extracutaneous involvement. Therapeutic choice includes observation, local or systemic therapy based on histology and disease extension. Patient management is multidisciplinary, including dermatologist, pathologist, hemato-oncologist and radiation oncologist.